Manifestation of High Endogenous Heparinization in Postpartum Hemorrhage Patient using Thromboelastography: New Avenue of Coagulopathy Monitoring - Yan, Tian; Fei, He; Changfu, Ji; Dong, Lai; Weng, Ching-Feng (Archives of Clinical and Medical Case Reports, 2023)
Background: Postpartum hemorrhage (PPH) is a leading cause of severe maternal morbidity and mortality worldwide which leads to massive blood loss. Coagulation abnormalities in response to severe trauma or infection are a latent cause that might aggravate PPH. Case Presentation: A 39-week menolipsis of a 26-year-old puerpera appeared lacking amniotic fluid and uterine infection after examination. During the cesarean section, the patient manifested fever, massive hemorrhage, and shock. The low coagulation of the PPH patient was diagnosed by thromboelastography (TEG) guided with heparinase (type I). According to the sequential monitoring via the TEG guided assay, the coagulopathy and hyper-heparinization were obviously shown. Concurrent protamine correction for the patient’s coagulation abnormality gradually resulted in a stable condition after 4 hours of emergent treatment. This setting revealed that TEG-guided determination of endogenous heparin and subsequent infusion of protamine effectively reverted the syndrome of PPH. Conclusions: This is an investigation of the PPH syndrome with infection patient suggests that hyper-endogenous heparinization should be clinically taken into consideration for low coagulation.